Evaluation of methylene blue solution distribution in the four-point transversus abdominis plane block technique in pigs: a pilot anatomical study - Sredenšek, Jerneja; Brankovič, Jana; Lampreht Tratar, Urša; Čemažar, Maja; Đokić, Mihajlo; Seliškar, Alenka (Frontiers in Veterinary Science, 2025)
AimThis prospective pilot anatomical study aimed to develop an ultrasound-guided transversus abdominis plane (TAP) block technique that desensitises cranial and mid-abdominal wall in grower pigs. We hypothesised that a four-point TAP approach would be more efficient than a three-point TAP in staining relevant nerves of the cranial and mid-abdominal wall.MethodsIn phase I, the ultrasound anatomy of the abdominal wall musculature was examined on three pig cadavers (two piglets and one fattening pig) and the ultrasound localization of the needle in the corresponding interfascial plane was practised. In phase II, a three-point TAP injection was performed in three freshly euthanized cadavers of grower pigs. A 1% methylene blue solution (0.3 mL/kg per injection point) was injected between the transversus abdominis and internal oblique muscle. In phase III, methylene blue solution was injected at four points (0.2 mL/kg per injection point) in four anaesthetized grower pigs prior to euthanasia. Positive nerve staining was defined as continuous staining of at least 1 cm of the nerve length. Binary variables (positive/negative) were used for nerve staining assessment.ResultsThe four-point TAP technique with a lower injection volume stained more nerves than the three-point technique with a higher injection volume, i.e., 69% of the observed nerves from the eighth-last thoracic to the third lumbar nerve were stained with the four-point TAP technique. The nerves in the centre were stained with a higher success rate, while the eighth-last thoracic and the second lumbar nerve were stained with less success (1/8 and 3/8, respectively). The third lumbar nerve was not stained.ConclusionThe four-point TAP technique could be used as part of a multimodal analgesia approach for cranial and mid-abdominal surgery in pigs, but live animal studies are needed to evaluate the clinical applicability and efficacy of desensitisation.